Perivascular spaces are associated with tau pathophysiology and synaptic dysfunction in early Alzheimer's continuum. (December 2021) - Vilor‐Tejedor, Natalia; Ciampa, Iacopo; Operto, Greg; Falcon, Carles; Suarez‐Calvet, Marc; Crous‐Bou, Marta; Shekari, Mahnaz; Arenaza‐Urquijo, Eider M.; Milà‐Alomà, Marta; Grau‐Rivera, Oriol; Minguillón, Carolina; Kollmorgen, Gwendlyn; et al.
Abstract: Background: Perivascular spaces (PVS) have an important role in the elimination of metabolic waste from the brain. However, the relationship between enlarged PVS (ePVS) and risk factors or pathophysiological mechanisms involved in Alzheimer's disease (AD) remains unknown. The aim of this study was to investigate the association between the ePVS, demographic and cardiovascular risk factors, cognitive performance and CSF biomarkers of several pathophysiological mechanisms for AD. Method: The study included 322 middle‐aged cognitively unimpaired participants from the ALFA+ study, many within the Alzheimer's continuum . The exploratory Roche NeuroToolKit assays, a panel of automated robust prototype assays, and Elecsys ® immunoassays were used to measure CSF Aβ42, Aβ40, p‐tau and t‐tau, NfL, neurogranin, TREM2, YKL40, GFAP, IL6, S100, and α‐synuclein. Cognitive performance was measured using a Preclinical Alzheimer Cognitive Composite (PACC) score. PVS in the basal ganglia (BG) and centrum semiovale (CS) were assessed based on a validated 4‐point visual rating scale [Figure 1]. Odds ratios were calculated for associations of cognitive performance, cardiovascular and AD risk factors with ePVS using logistic and multinomial models adjusted for relevant confounders. Models were stratified by Aβ status (positivity defined as Aβ42/40 < 0.071). Result: The degree of PVS enlargement significantly increased with age in both BG and CS regions independently of cardiovascular risk factors. Higher levels of p‐tau, t‐tau, and neurogranin were significantly associated with ePVS in the CS of Aβ‐positive individuals, after accounting for relevant confounders [Figure 2], but no other significant associations were found. Conclusion: Our results support that ePVS in the CS are associated with tau pathophysiology, and synaptic dysfunction in asymptomatic stages of the Alzheimer's continuum .